Control of Cdc28 CDK1 by a stress-induced lncRNA - Nadal-Ribelles, Mariona (2014)
Genomic analysis has revealed the existence of a large number of long non-coding RNAs (lncRNAs) with different functions in a variety of organisms, including yeast. Cells display dramatic changes of gene expression upon environmental changes. Upon osmostress, hundreds of stress-responsive genes are induced by the stress-activated protein kinase (SAPK) p38/Hog1. Using whole-genome tiling arrays, we found that Hog1 induces a set of lncRNAs upon stress. One of the genes expressing a Hog1-dependent lncRNAs in antisense orientation is CDC28, the CDK1 kinase that controls the cell cycle in yeast. Cdc28 lncRNA mediates the establishment of gene looping and the relocalization of Hog1 and RSC from the 3′UTR to the +1 nucleosome to induce CDC28 expression. The increase in the levels of Cdc28 results in cells able to re-enter the cell cycle more efficiently after stress. This may represent a general mechanism to prime expression of genes needed after stresses are alleviated.